Alternativas de encapsulamiento para lodos contaminados por hidrocarburos, generados en lavadoras y lubricadoras de la ciudad de Latacunga - Salazar Cajas, Jaime Bladimir (2017)
The research project "Encapsulation alternatives for sludge contaminated by hydrocarbons" was carried out using the sediments produced by the lubricators and washing machines of the urban area in the city of Latacunga, in the province of Cotopaxi. The objective was to evaluate the capacity to remove TPH (Total Hydrocarbons of Petroleum) applying two methods of remediation: Physical chemistry (stabilization and solidification) and Biological (biopiles).Samples of sludge were obtained from the lubricators and washing machines where these activities were carried out. The samples were homogenized and sent to the accredited laboratory for the analysis of the TPH concentration. The results showed that hydrocarbon concentrations do not comply with the current regulations according to Table No. 6 of the RSRAHO Executive Order 1215, which states that: TPH levels in sludge must be less than mg/kg for sensitive ecosystems, less than 2500 mg/kg for soils of agricultural use and less than 4000 mg/kg for industrial use. The treatment methods were evaluated at the end of 3 months (90 days). After this period, a pollutant concentrations analysis was conducted, to know the extraction capacity of Total Petroleum Hydrocarbons in the different tests. The comparison of the results of each treatment showed a noticeable decrease in the concentration of this contaminant because the P-value is less than 0.05, rejecting the null hypothesis with 95% confidence. In the physicochemical test, with the application of a commercial absorbent there was an average removal of 58%. The maximum capacity of removal presented was 75% and the minimum 43%. While with the application of the biopiles, this treatment presented an average removal of 42%. The maximum amount of removal was 51% and the minimum 24%. Both treatments were compared with the TPH values obtained from the control. The execution of this project seeks to generate interest to solve environmental problems present in activities carried out by lubricators and washing machines in the city of Latacunga projecting the prevention of natural resources.